Penerapan Metode Snowball Throwing dalam Pembelajaran Mengidentifikasi Informasi Teks Eksplanasi pada Peserta didik kelas VIII SMP Negeri 2 Duhiadaa Satap Tahun Pelajaran 2024/2025: Penelitian - Febrianty Oka; Supriyadi; Salam (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to describe the results of implementing the snowball throwing method in teaching students to identify information in explanatory texts among eighth-grade students at SMP Negeri 2 Duhiadaa Satap in the 2024/2025 academic year. The research employed a descriptive qualitative approach with data collection techniques including observation, documentation, and testing. The findings indicate that the application of the snowball throwing method had a positive impact on increasing student engagement and learning outcomes. Students became more active in discussions, asking and answering questions, and found it easier to understand the structure and content of explanatory texts. The average student learning outcome score was 78.35, which falls into the “very good” category. Most students achieved scores above the minimum competency standard. The classroom atmosphere also became more lively and enjoyable. Therefore, the snowball throwing method can be considered an effective alternative teaching strategy to improve students' ability to comprehend key information in explanatory texts.